DNA methylation profiling is a method of choice for molecular verification of pediatric WNT-activated medulloblastomas. Issue 2 (25th September 2018) - Korshunov, Andrey; Sahm, Felix; Zheludkova, Olga; Golanov, Andrey; Stichel, Damian; Schrimpf, Daniel; Ryzhova, Marina; Potapov, Alexander; Habel, Antje; Meyer, Jochen; Lichter, Peter; Jones, David T W; et al.
Abstract: Background: Wingless-activated medulloblastoma (WNT MB) represents a well-characterized molecular variant accounting for 10–15% of all MB and is associated with a favorable clinical outcome. Patients with localized WNT MBs could benefit from de-intensification of combined treatment, which would require an accurate diagnosis of these tumors. However, despite the presence of molecular features related with a WNT MB signature (nuclear ß-catenin immunoexpression, CTNNB1 mutation, and monosomy 6), a prompt and reliable diagnostic verification of these tumors is not yet feasible. Methods: In the current study, we analyzed 78 samples of WNT MB treated in a single institute through genome-wide DNA methylation and targeted next generation sequencing to elaborate an optimal method for WNT MB molecular verification. Results: We found that DNA methylation profiling discloses significant advantages for molecular diagnostic of WNT MB. All other "routine" methods applied, such as ß-catenin immunohistochemistry, CTNNB1 mutation analysis, and detection of monosomy 6, failed to identify all WNT MB cases. Survival analysis revealed that application of a reduced radiotherapy protocol for WNT MB treatment had no influence on patients' survival. Only one patient died due to local relapse but recurrent tumor was pathologically and molecularly diagnosed as a secondary glioblastoma. Conclusions: DNA methylation analysis should be considered as a method of choice for further clinically relevant stratification of WNT MB and for correct diagnosis of the recurrent tumors. WNT MB patients with localized disease could benefit from treatment de-intensification.